Open innovation in science and technology parks : the role of governance, local contexts and multinational enterprises in a cross-country case study - Tomelin, Jurema, 1972- (2019)
Tese - Universidade Regional de Blumenau, Universidade Regional de Blumenau, Programa de Pós-Graduação em Ciências Contábeis, Blumenau, 2019.